Brucellosis: An Unrecognized Zoonotic Disease in Indonesia - Susan Maphilindawati Noor (Indonesian Center for Animal Research and Development, 2006)
Brucellosis, a bacterial zoonosis, is a disease caused by members of the genus Brucella . In Indonesia, brucellosis has known as a contagious reproductive disease in animals, however, only certain people know that brucellosis can be transmitted to human . Bovine brucellosis is characterised by one or more of the following signs : abortion, retained placenta . orchitis, epididymitis and, rarely, arthritis, with excretion of the organisms in uterine discharges and in milk . The Brucella organism is transmitted to human most commonly by ingestion of untreated milk or milk products or through the mucous membranes and wound of the skin . The severity of human disease varies, depending largely upon the infecting strain . Brucella abortus, B . melitensis. B . suis and B. canis are highly pathogenic for humans . Clinical symptoms of human brucellosis may include an intermittent fever, headaches, weakness, arthalgia, myalgia and weight loss . Occasional complications include arthritis, endocarditis, hepatitis granuloma, meningitis, orchitis dan osteomyelitis have also been reported . Brucellosis can also produce spontaneous abortion in pregnant woman . Diagnosis is based on the isolation of the organism and serology . Antibiotics are usually the mainstay of treatment and long-term treatment may be required . Brucellosis can be controlled by comprehensive campaigns to eradicate the disease by vaccination programme followed by test and slaughter of domestic animals which exhibit positive serologic reactions to brucellae. Key words : Brucellosis, zoonosis, diagnose, control